Reasons for tubal sterilisation, regret and depressive symptoms - Shreffler, Karina M. (J Reprod Infant Psychol, 2016)
OBJECTIVE: To examine the associations between sterilisation reasons, regret, and depressive symptoms. STUDY DESIGN: Black, Hispanic, and non-Hispanic White US women ages 25–45 who participated in the National Survey of Fertility Barriers (NSFB) and reported a tubal sterilisation surgery were included in the sample for this study (n=837). Logistic regression was used to examine how characteristics of the sterilisation surgery (reasons for sterilisation, time since sterilisation, and new relationship since sterilisation) are associated with the odds of sterilisation regret, and linear regression was used to examine associations between sterilisation regret, sociodemographic factors, and depressive symptoms. RESULTS: Findings revealed that 28 percent of U.S. women who have undergone tubal sterilisation report regret. Time since sterilisation and having a reason for sterilisation other than simply not wanting (more) children (e.g., situational factors, health problems, encouragement by others, and other reasons) are associated with significantly higher odds of sterilisation regret. Finally, sterilisation regret is significantly associated with depressive symptoms after controlling for sociodemographic characteristics. CONCLUSION: Sterilisation regret is relatively common among women who have undergone tubal sterilisation, and regret is linked to elevated, but not necessarily clinical depressive symptoms. The reasons for sterilisation can have important implications for women’s sterilisation regret and associated depressive symptoms.